Henry James's Europe Heritage and Transfer - Tredy, Dennis; Harding, Adrian; Duperray, Annick (Open Book Publishers, 2011)
As an American author who chose to live in Europe, Henry James frequently wrote about cultural differences between the Old and New World. The plight of bewildered Americans adrift on a sea of European sophistication became a regular theme in his fiction. This collection of twenty-four papers from some of the world's leading James scholars offers a comprehensive picture of the author's cross-cultural aesthetics. It provides detailed analyses of James's perception of Europe-of its people and places, its history and culture, its artists and thinkers, its aesthetics and its ethics-which ultimately lead to a profound reevaluation of his writing.